Age and Gender Specific Pulmonary and Extrapulmonary Tuberculosis in a Rural Area of Bangladesh (Journal of Rangpur Medical College, 2025)
Background: Tuberculosis (TB) remains a major public health concern in Bangladesh, with significant variability in its demographic, clinical, and management aspects. Objective: This study aims to assess the age and genderspecific burden of TB in a rural Bangladeshi population, emphasizing diagnostic approaches, symptom variation, and management strategies. Methods: This retrospective study was conducted from October 1, 2023, to September 30, 2024, at the Directly Observed Treatment, Short Course (DOTS) Centre of Kumudini Hospital, Mirzapur, Tangail, Bangladesh. A total of 429 participants (356 adults, 73 children) were diagnosed and managed under DOTS, with data collected via clinical evaluations, X-rays, MT, GeneXpert, FNAC, and ADA tests, and analyzed using SPSS 26. Results: Pulmonary TB (PTB) accounted for 53.85% of cases, with 37.30% bacteriologically confirmed and 16.55% clinically diagnosed. Extrapulmonary TB (EPTB) constituted 46.15% of cases, with cervical lymph node TB being the most prevalent subtype (83.33% of EPTB cases). Age distribution showed a higher burden of PTB in individuals aged >65 years (22.50% bacteriologically confirmed and 32.39% clinically diagnosed), whereas EPTB was most frequent among participants aged 25–